The invariant chain p35 isoform promotes formation of nonameric complexes with MHC II molecules. Issue 6 (18th March 2014) - Cloutier, Maryse; Gauthier, Catherine; Fortin, Jean‐Simon; Thibodeau, Jacques
Abstract : Four different isoforms of the human invariant chain (Ii) have been described (p33, p35, p41 and p43). These heterotrimerize in the endoplasmic reticulum (ER) before associating with MHC class II molecules (MHCIIs). However, the final stoichiometry of the Ii/MHCII complex remains debated. This is particularly interesting as both p35 and p43 include a di‐arginine motif that requires masking by MHCII to allow ER egress. Here, to functionally address the requirement for stoichiometric interactions, we used a recombinant DR heterodimer bearing its own cytoplasmic di‐lysine ER‐retention motif (DRKKAA ). When coexpressed with p33 and a control myc‐tagged DR (DRmyc ), DRKKAA was retained in the ER but had little impact on surface expression of DRmyc . However, when coexpressed with p35, DRKKAA restricted the surface expression of DRmyc, indicating that Ii trimers can be loaded with more than one MHCII. Similar results were obtained using HLA‐DQ instead of DRmyc, showing that a single trimeric Ii scaffold can include distinct MHCII isotypes. Altogether, these results demonstrate that the subunit stoichiometry of oligomeric Ii/MHCII complexes is influenced by p35.